2018
DOI: 10.5194/bg-2018-341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic high-frequency measurements of full soil greenhouse gas fluxes in a tropical forest

Abstract: Abstract. Measuring in situ soil fluxes of carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) continuously at high frequency requires appropriate technology. We tested the combination of a commercial automated soil CO2 flux chamber system (LI-8100A) with a CH4 and N2O analyzer (Picarro G2308) in a tropical rainforest for 4 months. A chamber closure time of 2 minutes was sufficient for a reliable estimation of CO2 and CH4 fluxes (100% and 98.5% of fluxes were above Minimum Detectable Flux -MDF, respec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Consequently, disentangling the responses of soil respiration to environmental variation has been difficult, as biophysical drivers such as light, temperature, and moisture tend to covary both in space and time (Davidson & Holbrook, 2009; Kuzyakov & Gavrichkova, 2010; Savage et al, 2009; Zhang et al, 2018). A promising approach for identifying the most important biophysical drivers of soil respiration in tropical moist forests are automated chambers measuring at high temporal frequency, with concomitant measurements of biophysical variables in the soil and canopy environment (Carbone & Vargas, 2008; Courtois et al, 2019; Rubio & Detto, 2017; Savage et al, 2009; Savage et al, 2014; Vargas & Allen, 2008a; Wood et al, 2013). In tropical moist forests, these data are especially valuable, as hourly measurements of soil respiration with seasonal resolution are scarce (but see Raich, 2017; Rubio & Detto, 2017; Zanchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, disentangling the responses of soil respiration to environmental variation has been difficult, as biophysical drivers such as light, temperature, and moisture tend to covary both in space and time (Davidson & Holbrook, 2009; Kuzyakov & Gavrichkova, 2010; Savage et al, 2009; Zhang et al, 2018). A promising approach for identifying the most important biophysical drivers of soil respiration in tropical moist forests are automated chambers measuring at high temporal frequency, with concomitant measurements of biophysical variables in the soil and canopy environment (Carbone & Vargas, 2008; Courtois et al, 2019; Rubio & Detto, 2017; Savage et al, 2009; Savage et al, 2014; Vargas & Allen, 2008a; Wood et al, 2013). In tropical moist forests, these data are especially valuable, as hourly measurements of soil respiration with seasonal resolution are scarce (but see Raich, 2017; Rubio & Detto, 2017; Zanchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the Guyaflux site, a temperature sensor (CS107; Campbell Scientific Inc., Logan, UT, USA) and soil moisture sensors (CS616, Campbell Scientific Inc.) were used to measure soil temperature and volumetric water content at 0–5 cm soil depth. The instrumented tree was selected because of its proximity (< 15 m) to the soil flux system that had previously been set up at the site (Courtois et al, 2019), its size (50.1 cm DBH, thus being classed as ‘medium’ sized) and the fact that the species, Eperua falcata , is a member of the Fabaceae family, one of the most common tree families in the area; Ter Steege et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…automated chambers) have recently proven to be effective in situ . Courtois et al, (2019) reported that the combination of a commercial soil GHG chamber system, an automated soil CO 2 flux system (LI‐8100A) running in parallel with a cavity ring‐down spectroscopy (CRDS) instrument (Picarro G2308) measuring CH 4 and N 2 O fluxes, showed great potential to measure continuously and simultaneously the three GHG fluxes at multiple soil locations under tropical conditions. In that study, substantial efforts were made to determine the optimal chamber closure time for each of the three GHGs, where long closure times (> 20 min) gave reliable, although low, soil N 2 O flux estimates, whereas short closure times (< 2 min) were sufficient to yield accurate estimates of soil CO 2 and CH 4 fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent automated chamber development is the combination of relatively small‐diameter (∼20 cm) autochambers, originally designed for soil respiration measurements, and connected to a cavity ring‐down spectroscopy (CRDS) instrument to measure CH 4 and N 2 O concentrations (Courtois et al., 2019). Due to the high sensitivity of the CRDS instrument, a 2‐min chamber closure time was sufficient to measure CH 4 concentrations, but for N 2 O, a 25‐min closure period was required in low‐N 2 O‐flux ecosystems, such as tropical forests.…”
Section: Detection Limitsmentioning
confidence: 99%